Study of genetic variability of umbilical cord blood using RAPD assay (Bangladesh Journal of Medical Science, 2021)
Background: The genetic variability of Umbilical Cord Blood (UCB) is most important for newborn screening, therapeutic possibility of haematological disorders as well as for the establishment of cord blood banking and stem cell research.Method: Genetic variability of umbilical cord blood (UCB) of 22 human subjects was evaluated first time by applying Random Amplified Polymorphic DNA (RAPD) assay using six decamar primers (B-14, OPB-05, OPB-08, OPB-12, OPB-19 and UBC-122).Result: A total number of bands were recorded 312 from 116 polymorphic loci and single monomorphic locus. All the markers showed highest polymorphism (100%) except the primer OPB 08 (92.31%) among tested individuals. The genetic distance was observed with highest 1.0 and lowest 0.72 respectively whereas mean genetic distance was recorded 0.90. Considering Shannon-Wiener index average diversity was recorded 0.139365. The mean Nei genetic similarity was found 0.17 which was found opposition to genetic distances. A phylogenetic relationship among the individual subjects was also observed between the linkage distances of 11 to 27 with 8 clades, 3 subclusters and a cluster. In addition, average allele frequency p and q was observed 0.08156 and 0.948751 respectively whereas highest intra locus gene diversity and average gene diversity were found 3.323817 and 0.144572 respectively.Conclusion: Considering different parameters, higher genetic variability was found among the experimental subjects, probably due to the mixture DNA of parents and newborn.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.848-854